2002
DOI: 10.2114/jpa.21.115
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study on Relationship between the Hours of Sleep and Life Style Factors in Japanese Factory Workers.

Abstract: To prevent "life style-related diseases", it is necessary to evaluate not only the factors directly related to sleep but also the relationship between sleep and other life style-related factors (such as smoking, alcohol drinking, food habits, and exercise routines). There have b e e n n o e x t e n si v e st ud i e s c o n d u c t e d o n t h e s e relationships. A survey was conducted on 2,000 employees of a large plant over a 6-year period to provide data that would allow one to analyze correlation between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
82
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 22 publications
14
82
2
6
Order By: Relevance
“…One was MEDLINE for use in search of research paper published in 1966-2004, studying Japanese working subjects, written in either English or Japanese. The other was Igaku Chuo Zasshi CD-ROM database, in which Japan Centra Revuo Medicina covered 2,360 medical, dental and pharmacological periodicals published in Japan between 1987 Y DOI Industrial Health 2005, 43, [3][4][5][6][7][8][9][10] and 2004. The following terms combined were searched in article titles and keywords to single out the articles reviewed: sleep AND epidemiology AND Japan* AND [work*, employ* or job].…”
Section: Methods Of Studies Searchedmentioning
confidence: 99%
See 2 more Smart Citations
“…One was MEDLINE for use in search of research paper published in 1966-2004, studying Japanese working subjects, written in either English or Japanese. The other was Igaku Chuo Zasshi CD-ROM database, in which Japan Centra Revuo Medicina covered 2,360 medical, dental and pharmacological periodicals published in Japan between 1987 Y DOI Industrial Health 2005, 43, [3][4][5][6][7][8][9][10] and 2004. The following terms combined were searched in article titles and keywords to single out the articles reviewed: sleep AND epidemiology AND Japan* AND [work*, employ* or job].…”
Section: Methods Of Studies Searchedmentioning
confidence: 99%
“…Most of the studies reviewed here tried to detect risk or associated factors of sleep problems (e.g., DIS, DMS, EMA, insomnia, poor sleep quality, EDS) 5-7, 9-14, 16-25, 27, 28) and sleep length 8,15,26) . Main research topics on sleep correlates in the studies for non-shift workers could be categorized into four: (1) pathophysiology [5][6][7]9) ; (2) lifestyle behaviors 5,8,14,17) ; (3) job-related conditions 5, 6, 10-13 15) ; and (4) psychopathology 5,6,10,16,17) .…”
Section: ) Non-shift Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, more sleep is associated with increased levels of physical activity, 5,6 although one epidemiological study did not see this association. 7 While more research has assessed the infl uence of physical activity on sleep, the relationship between the two factors has been proposed to be bidirectional, 8 and a growing literature supports the effects of sleep on physical activity. For example, a recent study of 11 women with insomnia tracked for 16 weeks demonstrated that sleep infl uenced next day exercise (i.e., longer sleep onset was associated with shorter next-day exercise duration); interestingly, in this sample, exercise did not have an effect on subsequent sleep.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Studies have shown that short sleepers have higher energy intakes, notably from fat (4,5) and snacks (6), than do normal sleepers. NHANES data in the United States showed that short sleepers, generally defined as those who sleep <7 h/night, consume a smaller variety of foods, with lower protein, carbohydrate, fiber, and fat intakes relative to normal sleepers who report 7-8 h of sleep/night (7).…”
Section: Introductionmentioning
confidence: 99%